Effects of chemotherapy process on postural balance control in patients with breast cancer - (:unkn) unknown (Wolters Kluwer Medknow Publications, 2019)
Breast cancer (BC) is the most common type of cancer among women in the world. Patients can face musculoskeletal disorders due to treatment side effects that result in failure to walk, falling, or fractures associated with balance problems. PURPOSE: The aim of this study was to determine whether postural balance would be affected during chemotherapy (CT) in people with BC. MATERİALS AND METHODS: A total of 32 women who consulted the medical oncology department, between 31 and 63 years of age, were admitted to the study. For fear of falling, fall efficiacy scale; for static balance, double-leg, single-leg, and tandem stance tests with eyes opened and eyes closed; Romberg test; for dinamic balance, Sit To Stand (STS) test, and Time Up and Go (TUG) tests were performed in the patients. RESULTS: Reduced fear of falling between CT cycles (P < 0.0125), no change in postural sway in double-leg stance test with eyes opened (P = 0.734) and eyes closed (P = 0.127), significantly increased postural instability in single-leg and tandem stance test with eyes opened and eyes closed (P = 0.000), no change in postural stability in Romberg test (P > 0.05), significantly increased postural instability in STS (P = 0.000) and TUG tests (P = 0.000), and significantly increased time of finishing the STS (P = 0.021) and TUG tests (P = 0.010) were noted. CONCLUSİON: Patients demonstrated postural instability which can ruin the daily life activities in many parameters of measurements. Postural balance exercises should be performed by BC survivors undergoing CT. © 2019 Indian Journal of Cancer | Published by Wolters Kluwer - Medknow.
Keywords: Breast neoplasms; chemotherapy; postural balance